The Effectiveness of Collaborative Strategic Reading (CSR) in Improving Students’ Reading Comprehension of Recount Texts - M. Saiful Nurhadi; Wiwin Indiarti; Muhammad Farhan Syach; Linda Ratnasari (LUNAR, 2026)
This study examines the effectiveness of Collaborative Strategic Reading (CSR) in improving students’ comprehension of recount texts in an Indonesian English as a Foreign Language (EFL) context. Employing a pre-experimental one-group pretest–posttest design, the study involved 21 tenth-grade students of MA Al-Qodiri 8 Kelir, Banyuwangi, selected through purposive sampling. Data were collected using a reading comprehension test consisting of 20 multiple-choice items aligned with key comprehension indicators and administered before and after the CSR intervention. The data were analyzed using descriptive statistics and a paired-sample t-test. The results show a substantial improvement in students’ reading performance, with the mean score increasing from 58.10 in the pretest to 74.76 in the posttest. Statistical analysis indicates that the improvement is significant (p < 0.05), confirming the effectiveness of CSR. In addition to quantitative gains, CSR also enhances students’ meta-cognitive awareness and supports collaborative meaning-making during reading activities. These findings suggest that CSR not only improves comprehension outcomes but also promotes active and strategic learning. Therefore, CSR can be considered an effective alternative instructional strategy for improving reading comprehension in EFL classrooms.